Overcoming the Challenge of Support Surface Selection: Utilization of Standards. (October 2021) - Thurman, Kristen; Deppisch, Michelle; Morello, Susan S.; Moseley, Rachel; Slayton, Stephanie; Sylvia, Cynthia; Todd, Jackie
Abstract : Supplemental digital content is available in the text. ABSTRACT: Selecting the appropriate support surface for patients continues to challenge clinicians and facilities. The Support Surface Standards Committee has developed and published test methods that allow for informed comparisons among support surface characteristics. The first published standards address the performance characteristics of immersion/envelopment, shear/friction, and microclimate management. This article describes the full body support surface standards development and provides guidance on the use of the outcomes from those standard tests for clinicians and facilities to make more informed choices for patients and patient populations.